Respostas

2014-06-29T17:52:42-03:00
 \frac{4}{6} + \frac{3}{6} - \frac{1}{3}

mmc de 3 e 6 =

3,¨6| 2==== 2 x3 =6
3,3   3
1

 \frac{4+3-2}{6} = \frac{5}{6}
1 5 1
2014-06-30T02:33:37-03:00
Bom dia !!!


 \frac{4}{6}  +  \frac{3}{6} -  \frac{1}{3}

Temos que fazer mmc (mínimo múltiplo comum de 3 e 6 )

3,  6   | 2     agora multiplica-se : 2 x 3 = 6, 6 é o mmc  de 3 e 6
3,  3     3
1,1


 \frac{4}{6} + \frac{3}{6} - \frac{1}{3}

 \frac{1.4+1.3 - 2.1 }{6} = \frac{4+3-2}{6} = \frac{5}{6}



Resposta:  \frac{4}{6} + \frac{3}{6} - \frac{1}{3} = \frac{5}{6}